Sentenças de Negação com É ruim e Nem a pau no Português Brasileiro - Marcelino, Nara Juscely Minervino de Carvalho (2018)
This thesis proposes to analyze the syntactic configuration and the semantic compatibility between the Sentences of Denial of Brazilian Portuguese (PB) carried out with the markers é ruim and nem a pau and the context in which these sentences are inserted, considering, among others, the assumptions of Generative Grammar. In PB, denial sentences are divided into Propositional Negation Sentences (PNS), Regular Negation Sentences (RNS), Metalinguistic Negation Sentences (MNS), Emphatic Negation Sentences (ENS) and Anaphoric Negation Sentences (ANS). Sentences with é ruim and nem a pau are, mostly, Metalinguistic Negation Sentences, once they can only be effected through the existence of a presupposition concretely realized, establishing contrast to the propositional content of the presupposition, so as to rectify some variable of its truth value. In view of the syntactic projection of a sentence, the é ruim is always projected in Complementizer Phrase (CP) since is established in a full Inflectional Phrase (IP) whose main verb appears in the Indicative, with nucleus and arguments properly occupying their positions. The nem a pau, in turn, now it appears in CP, now in Adverbial Phrase (AdvP), as an adjunct constituent. Although they are constituents that establish negation, these markers can originate in distinct positions, which depend on whether they are peripheral constituents or adjunct. If peripherals, they suffer external merge in CP, where they also occur. If adjunct, they are attached to some maximum projection, upon which it inserts its scope. Among these markers, the é ruim is always a peripheral Metalinguistic Negation Marker (MNM), generated and performed directly in CP. The nem a pau, however, is a peripheral or adjunct constituent. Therefore, depending on the position in which it takes place, whether above or below the verb, and the presupposition that precedes it, if an affirmation or negation sentence, the nem a pau can be an MNM, an MNR or an IPN. If the presupposition is a sentence of affirmation, it is an MNM or an MNR only if it is above the verb. If it is below the verb, it is a Negative Polarity Item (IPN) that relates to the “no” that denies the assertion of the assumed table. In all cases, the nem a pau is a peripheral marker. If the presupposition is a negation sentence, the nem a pau also has an MNM, MNR, or IPN reading, however it is an MNM or an MNR if it appears above the verb, hence it is a peripheral marker. If it is below the verb, it is an IPN that denies the negation in the assumption, generated in the adjunct position.